Performance Management and Monitoring of Internal Audit for the Public Sector in Romania - Elena Doina Dascalu; Nicu Marcu; Ioan Hurjui (Amfiteatru Economic Journal, 2016)
Performance management is an on-going process, which has an essential component part, performance measurement, which involves the identification, supervision and communication of performance results, through the relation to a set of performance indicators. Based on the assessment results, corrective measures are established to ensure attainment of targeted results, offering a feedback, essential for the decision grounding enhancement, at all levels: strategic, operational or individual. As concerns performance management in public institutions in Romania, The Code on managerial internal control provides a hierarchy type model, in the framework of which, the head of the public entity, which is on the first level, needs to provide for performance monitoring for each objective and activity, through the intermediary of relevant quantitative and qualitative indicators, including referring to economy, efficiency, and effectiveness. Given the importance of the internal audit in the process of performance management, identifying solutions for continuous improvement of the public internal audit was subject to a study that was based on questioning public sector auditors on how to monitor the performance of public internal audit activity. Considering issues arising, the article proposes a series of directions for improving the monitoring of the performance of public internal audit activity in the public sector.
Keywords: H83; M42; M48; 330; Code of managerial internal control; public internal audit; performance measurement; set of performance indicators; performance monitoring; continuous improvement